Religion in secular society: Fifty years on - Wilson, Bryan R.; Bruce, Steve (Oxford Oxford University Press, 2016)
Fifty years after its publication, Bryan Wilson's Religion in Secular Society (1966) remains a seminal work. It is one of the clearest articulations of the secularization thesis: the claim that modernizations brings with it fundamental changes in the nature and status of religion. For Wilson, secularization refers to the fact that religion has lost influence at the societal, the institutional, and the individual level.